2019
DOI: 10.1039/c9ta02237f
|View full text |Cite
|
Sign up to set email alerts
|

Partially fluorinated MIL-101(Cr): from a miniscule structure modification to a huge chemical environment transformation inspected by 129Xe NMR

Abstract: Partial fluorine functionalisation of MIL-101(Cr) was successfully achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…The effect of electron‐withdrawing groups was impressively demonstrated by Lima and co‐workers exploiting the high xenon polarizability. [ 112 ] Investigating a mixed linker MIL‐101(Cr) containing terephthalic acid and only 1% tetrafluoroterephthalic acid, they found a chemical shift of xenon adsorbed in the pores shifting downfield by 38 ppm, clearly evidencing the incorporation of the fluorinated linker. In addition, the paramagnetic Cr III centers were found to induce a paramagnetic shift not only to the adsorbed Xe, but also a shift of 10–20 ppm to gas phase xenon in inter‐particle voids.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…The effect of electron‐withdrawing groups was impressively demonstrated by Lima and co‐workers exploiting the high xenon polarizability. [ 112 ] Investigating a mixed linker MIL‐101(Cr) containing terephthalic acid and only 1% tetrafluoroterephthalic acid, they found a chemical shift of xenon adsorbed in the pores shifting downfield by 38 ppm, clearly evidencing the incorporation of the fluorinated linker. In addition, the paramagnetic Cr III centers were found to induce a paramagnetic shift not only to the adsorbed Xe, but also a shift of 10–20 ppm to gas phase xenon in inter‐particle voids.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…In a recent work, Díaz-Ramírez et al [66] reported the partial functionalization of MIL−101(Cr) with fluorine using 2,3,5,6-tetrafluoro−1,4-benzenedicarboxylate (BDC-4F) providing MIL−101(Cr)-4F(1%). Cyclic voltammetry measurements showed that the acidity of the metal centers of the modified form of the MOF was improved.…”
Section: H2s Capture Via Materials Of the Institute Lavoisier (Mils)mentioning
confidence: 99%
“…Adsorption capacities of several materials towards H 2 S molecules (green: zeolites, yellow: metal oxides, red: MOFs, blue: activated carbons): (a) Zeolite 13X[64], (b) Zeolite 4A[64], (c) PEI(50)/MCM-48[116], (d) SAPO-43[117], (e) iron sponge[118], (f) Cu 0.5 Zn 0.5 /Al 2 O 3[119], (g) MIL-53(Al)-TDC[114], (h) MIL−101(Cr)[49], (i) MIL−101(Cr)-4F(1%)[66], (j) MIL-47(V)[49], (k) AC (Desorex K43-Na)[120], and (l) AC (Desorex K43-BG)[120].…”
mentioning
confidence: 99%
“…This material is the result of the successful partial uorination of MIL-101(Cr); which we achieved recently. 18 MIL-101(Cr)-4F(1%) showed an increased hydrophobicity and a higher selectivity towards CO 2 in anhydrous conditions when compared to its pristine form MIL-101(Cr). 18 Furthermore, MIL-101(Cr) based composites have shown outstanding catalytic activity (96.5% yield) in the conversion of terminal alkynes into propiolic acids with CO 2 , as well as in several other carbon conversion reactions.…”
Section: Introductionmentioning
confidence: 97%